Effects of Buoyancy Flux on Upper‐Ocean Turbulent Mixing Generated by Non‐Breaking Surface Waves Observed in the South China Sea. Issue 5 (13th May 2021) - Zhuang, Zhanpeng; Yuan, Yeli; Zheng, Quanan; Zhou, Chaojie; Zhao, Xinhua; Zhang, Ting
Abstract: The surface waves are the most energetic motions, which have great contribution to the turbulent mixing in the upper ocean. In this study, a novel turbulent mixing scheme is proposed in terms of the non‐breaking wave velocity shear module with the buoyancy flux. In the scheme, the mixing coefficients can be calculated empirically from the significant wave height, the wave number, the wave frequency, the buoyancy frequency, and the turbulence Prandtl number. The buoyancy fluxes, as well as the non‐breaking wave velocity shear production, are important for the upper‐ocean turbulent mixing, and make the calculated turbulence dissipation rate closer to in situ observations, which are provided by the "Responses of Marine Hazards to Climate Change in the Western Pacific (ROSE)" Project. The effects of the buoyancy flux on the turbulent mixing are examined based on three numerical experiments using the MASNUM ocean model. In the experiments, the topography, the lateral boundaries, initialization conditions, and the surface forcing fluxes are taken from the GEBCO, HYCOM/NCODA, and ERA5 data, respectively. Comparing to the AVHRR remote sensing sea surface temperature (SST) products and in situ observations, the simulated results with the non‐breaking wave‐generated turbulent mixing gain significant improvement in the SST, upper‐ocean temperature structure, and the mixed layer compared with the classic Mellor‐Yamada scheme. The results show that the buoyancy flux is able to suppress the enhanced non‐breaking wave‐generated turbulent mixing, so that the improved model simulates the observations better than that without the buoyancy effects. Plain Language Summary: The sea surface waves can transfer the energy from the wave fields to turbulent mixing in the upper ocean. A novel turbulent mixing scheme is proposed in terms of non‐breaking wave velocity shear module with buoyancy flux. The simulated results from the ocean circulation model with the novel scheme gain significant improvement in the SST and the upper‐ocean temperature structure compared with the classic Mellor‐Yamada scheme. Buoyancy flux slightly suppresses the enhanced vertical mixing induced by non‐breaking wave‐generated turbulence, so that the improved model simulates the observations much better than that without the buoyancy effects. Key Points: A novel turbulent mixing scheme is proposed in terms of non‐breaking wave velocity shear module with buoyancy flux Buoyancy flux suppresses the over enhanced vertical mixing induced by non‐breaking wave‐generated turbulence Non‐breaking wave‐induced mixing with buoyancy flux improves simulated upper‐ocean temperature structure